Effects of preparation processes on the structure and properties of collagen gel. Issue 9 (4th July 2018) - Xu, Chengzhi; Nan, Jie; Dai, Chun; Wei, Benmei; Zhang, Juntao; He, Lang; Wang, Haibo
ABSTRACT: In this study, the effects of collagen self-assembly, drying methods, and reswelling on collagen gel structure and biological properties were determined. The results showed that the self-assembly of collagen improved the regularity and pore size of the collagen gel and promoted collagen gel thermostability and cell proliferation. After drying and reswelling, the main structure of the self-assembly gel was composed of lamellar gel walls, but the gel structure shrank to some extent and pore size was reduced. The structure of the self-assembled gel after drying and reswelling was closely related to that of the drying method.